Islamic Epistemology Paradigm: Worldview of Interdisciplinary Islamic Studies Syed Muhammad Naqueb Al-Attas - Mahmudin Mahmudin; Zayyadi Ahmad; Abdul Basit (International Journal of Social Science and Religion (IJSSR), 2021)
This article departs from the author's anxiety about Islamic epistemology vis a vis the Islamization of science in the worldview of interdisciplinary Islamic epistemology, Syed Muhammad Naqueb al-Attas regarding the Islamization paradigm of science with a concept with an approach based on the paradigm of Islamic epistemology. In this case, the problem of Islamization is fundamental epistemologically. However, al-Attas does not want to contradict one another, in fact, it further strengthens the Islamization of science under Islamic epistemology’s spirit or values. The epistemology of Islamic thought of Syed Muhammad Naqueb al-Attas regarding the concept of epistemology vis a vis the Islamization of science is not only built on revelation and religious belief. However, it is built on a cultural tradition strengthened by philosophical speculation related to secular life that focuses on humans as rational beings. As a result, science and ethical and moral values, governed by human reason, are constantly changing. Syed Muhammad Naquib Al-Attas’ Interdisciplinary Islamic Studies is a conception of the need for the Islamization of science related to reality and truth is understood by the unification method where there is a unity between inductive and deductive, empirical, and rational principles. The approach and theory used in this paper explore the historical roots of the epistemological paradigm of Syed Muhammad Naquib Al-Attas by combining esoteric and ecstical elements as well as the combination of secularism and religion. However, it must be an interdisciplinary scientific discipline in Islamic studies.